Myeloid MKL1 Disseminates Cues to Promote Cardiac Hypertrophy in Mice - Liu, Li; Zhao, Qianwen; Lin, Lin; Yang, Guang; Yu, Liming; Zhuo, Lili; Yang, Yuyu; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Cardiac hypertrophy is a key pathophysiological process in the heart in response to stress cues. Although taking place in cardiomyocytes, the hypertrophic response is influenced by other cell types, both within the heart and derived from circulation. In the present study we investigated the macrophage-specific roles of megakaryocytic leukemia 1 (MKL1) in cardiac hypertrophy. Following the transverse aortic constriction (TAC), myeloid MKL1 conditional knockout (MFCKO) mice exhibit an attenuated phenotype of cardiac hypertrophy compared to the WT mice. In accordance, the MFCKO mice were protected from excessive cardiac inflammation and fibrosis as opposed to the WT mice. Conditioned media collected from macrophages enhanced the pro-hypertrophic response in cardiomyocytes exposed to endothelin in an MKL1-dependent manner. Of interest, expression levels of macrophage derived miR-155, known to promote cardiac hypertrophy, were down-regulated in the MFCKO mice compared to the WT mice. MKL1 depletion or inhibition repressed miR-155 expression in macrophages. Mechanistically, MKL1 interacted with NF-B to activate miR-155 transcription in macrophages. In conclusion, our data suggest that MKL1 may contribute to pathological hypertrophy via regulating macrophage-derived miR-155 transcription.